Emergence of Klebsiella pneumoniae clinical isolates producing KPC‐2 carbapenemase in Cuba. Issue 4 (26th June 2014) - Quiñones, D.; Hart, M.; Espinosa, F.; Garcia, S.; Carmona, Y.; Ghosh, S.; Urushibara, N.; Kawaguchiya, M.; Kobayashi, N.
Abstract The emergence of Klebsiella pneumoniae producing carbapenemase (KPC) has now become a global concern. As a part of a nationwide multicentre surveillance study in Cuba, three K. pneumoniae clinical isolates resistant to carbapenems were detected for a 1‐month period (September to October 2011). PCR and sequence analysis revealed that the three strains harboured blaKPC‐2. They showed resistance or intermediate susceptibility to expanded‐spectrum cephalosporins, other β‐lactams, a β‐lactam/β‐lactamase inhibitor combination, and gentamicin. Two strains were susceptible only to colistin, whereas the other strain showing colistin resistance was susceptible to fluoroquinolones. These blaKPC‐2‐positive K. pneumoniae strains were classified into ST1271 (CC29), a novel clone harbouring blaKPC‐2, and were revealed to be genetically identical by PCR‐based DNA fingerprinting. The three patients infected with the KPC‐producing K. pneumoniae had common risk factors, and had no overseas travel experience outside Cuba, suggesting local acquisition of the resistant pathogen. This is the first report of a KPC‐producing K. pneumoniae in Cuba. Although detection of KPC in Enterobacteriaceae is still rare in Cuba, our finding indicated that KPC‐producing bacteria are a global concern and highlighted the need to identify these microorganisms in clinical laboratories.